The First World War in Spanish and British Textbooks: a Comparative Study of Skills, Historiographical Focus and the Sequencing of Activities - Webb, Philip Duncan (Historia y Memoria de la Educación, 2022)
This study compares a sample of Spanish and British textbooks to analyse how they present the topic of the First World War, a conflict that has distinct meanings in the national memory of both countries. With this aim, activities from the chosen textbooks are quantitively assessed with reference to two main variables: historiographical focus and the cognitive level required to complete them. To this we add another objective: to associate these variables with the position of different activities within the didactic sequence embedded in each textbook. The results confirm that both Spanish and British textbooks dedicate a large part of their activities to political-institutional history and military events. However, British books also incorporate a strong element of the history of everyday life, women’s history and “history from below”. In general, activities in British textbooks require a higher cognitive level than Spanish ones. Finally, introduction, extension and specific skills-based activities are more likely to require a high cognitive level than those found in the main body of a given teaching unit.